If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1) * 2 = 7 Reorder the terms: (-1 + 2x) * 2 = 7 Reorder the terms for easier multiplication: 2(-1 + 2x) = 7 (-1 * 2 + 2x * 2) = 7 (-2 + 4x) = 7 Solving -2 + 4x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = 7 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 7 + 2 4x = 7 + 2 Combine like terms: 7 + 2 = 9 4x = 9 Divide each side by '4'. x = 2.25 Simplifying x = 2.25
| 6.9x-2.6=18.1 | | 6x(2-x)=52 | | 25+4x=6x+9 | | 3(4x-1)-5(x+7)=3(x+1) | | x-1/5=x/2 | | 9/x=2/7 | | 4x+6*2-6=12x | | 9x-5=12y | | 5(6z-1)-5(z+1)=23(z+1) | | 4^3x-1=1/64 | | y^2+18y+45= | | 3000000=1.55x^2-5.1x+197 | | 4+8(x-6)=6-9(x-8) | | 5x-y^2-3=0 | | 3x+11y=33 | | (-7-3m^3-7m)-(-7m^3-3)=0 | | 3d*2+14d-5= | | 0.5(6x-20)+32=64 | | 5x^2+36x+2=0 | | 8x-44=-9x+78 | | 3x=18+4 | | 3x+4x=-3+x | | ln(3x-13)=16 | | v^2+3v-39=0 | | 3x+26=13-54 | | 3x(y^2+1)dx+y(x^2+2)dy=0 | | -8+15=5x-4x | | x^2+2ax-d^2=0 | | 4x+2=a | | 11=-4x-7x | | 5(-3)+8+3y=23 | | 0.5*x+1[(5x-4)(3x+2)]=0 |